O Papel Do Empowerment eda Comunicação Interna Na Performance dos Colaboradores: O Caso de uma Empresa Familiar Portuguesa - Martins, Marta; Campos Sobreira, Rosa Maria; Ribeiro, Neuza (My University, 2021)
Este estudo procura analisar a perceção dos colaboradores sobre o empowerment e a comunicação interna, bem como a relação entre estas variáveis e a performance dos colaboradores. Trata-se de uma pesquisa quantitativa com recurso ao inquérito por questionário na recolha de dados, assumindo o formato de estudo de caso. Participaram nesta pesquisa o total de colaboradores de uma pequena empresa familiar da indústria metalomecânica, na região Oeste de Portugal. Recorreu-se ao método de dupla fonte diminuindo os riscos da variância do método comum, ou seja, foram usadas díades chefia-colaborador para a obtenção dos dados relativos às variáveis em estudo. Assim, os colaboradores reportaram as suas perceções de empowerment e da comunicação interna; a performance dos colaboradores foi avaliada pelas respetivas chefias. Os resultados mostraram que: (a) os colaboradores apresentam elevados níveis de empowerment; (b) a comunicação interna apresenta níveis moderados pelo que se sugerem melhorias a esse nível; (c) o empowerment apresenta uma relação positiva com a performance dos colaboradores; (d) a comunicação interna não apresenta relação significativa com a performance.

This study seeks to analyze employees' perceptions of empowerment and internal communication, as well as the relationship between these variables and employee performance. In this sense, two specific objectives were defined: (1) to identify the perception of employees about their empowerment and the company's internal communication; (2) to understand if empowerment and internalcommunication have any impact on employee performance. This is a quantitative research using a questionnaire survey for data collection, assuming the format of a case study. The total number of employees of a small family company in the metal-mechanic industry, in the western region of Portugal, participated in this research. The dual-source method was used to reduce the risks of variance of the common method, that is, manager-employee dyads were used to obtain data on the variables under study. Thus, employees reported their perceptions of empowerment and internal communication; the performance of employees was evaluated by their supervisors. The results showed that: (a) employees have high levels of empowerment; (b) internal communication has moderate levels so that improvements at this level are suggested; (c) empowerment has a positive relationship with employee performance; (d) internal communication has no significant relationship with performance. The results of this research, in addition to contributing to knowledge in the area of people management, may support policies of employee empowerment and internal communication in this particular company, as well as in other family-owned SMEs.
Keywords: Empowerment; Comunicação interna; Performance; Empresa familiar